Malay songket motif: a design and acumen of weavers / Arba’iyah Ab. Aziz - Ab. Aziz, Arba’iyah Ab. Aziz (Universiti Teknologi MARA, 2019)
In the Malay community, songket has already been recognized and labelled as the Queen of Fabrics. The uniqueness of the songket lies within the creative arrangement and beautiful creation of motifs that suit the person who adorns this piece of fabric. For some, the songket symbolises the Malay civilization and values. Thus, this paperwork seeks to identify the weavers’ selections of Malay songket motifs in terms of meaning, philosophy, religion, beliefs, customs, norms, values, taboos, and the worldview of the Malays. The motifs are the manifestations of the close bond between the Malays and their surroundings as well as their life experiences. Every identification and classification of this artwork will lead to the development of human resources and the sustainability of art heritage especially to scholars, teachers, weavers, artists, cultural enthusiasts and patrons, art historians, art creators, and the community in general. Besides establishing the recognition of songket weavers’ skills and abilities, this paper seeks to elevate the awareness of preservation and appreciation of wearing songket as a long-lasting legacy.